DRUG-INDUCED LIVER INJURY IN THE CONTEXT OF OSTEOARTHRITIS: A LITERATURE REVIEW (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Drug-induced liver injury (DILI) is a significant complication in patients undergoing long-term pharmacotherapy, especially those diagnosed with osteoarthritis (OA). OA, one of the most prevalent degenerative joint diseases in the elderly population, often requires chronic administration of nonsteroidal anti-inflammatory drugs (NSAIDs), analgesics, and adjunctive medications. This review examines the mechanisms, risks, and classifications of DILI, with a focus on commonly used pharmacological agents in OA management. The pathophysiological processes of OA, treatment protocols, and implications of hepatotoxicity are analyzed to improve clinical decision-making and minimize liver-related adverse outcomes.